Action for Health in Diabetes (Look AHEAD) Trial: Baseline evaluation of selected nutrients and food group intake - Vitolins, Mara Z. (2009)
BACKGROUND: Little has been reported regarding food and nutrient intake in persons diagnosed with type 2 diabetes and most reports have been based on findings in select groups or persons who self-reported having diabetes. OBJECTIVE: To describe the baseline food and nutrient intake of the Look AHEAD trial participants, compare participant intake to national guidelines, and describe demographic and health characteristics associated with food group consumption. METHODS: The Look AHEAD trial is evaluating the effects of a lifestyle intervention (calorie control and increased physical activity for weight loss) compared to diabetes support and education on long-term cardiovascular and other health outcomes. Participants are 45-75 years old, overweight or obese [Body Mass Index (BMI) ≥ 25 kg/m(2)], and have type 2 diabetes. Baseline food consumption was assessed in 2,757 participants between September 2000 and December 2003 by food frequency questionnaire in this cross-sectional analysis. STATISTICAL ANALYSIS: Descriptive statistics were used to summarize intake by demographic characteristics. Kruskal-Wallis tests assessed univariate effects of characteristics on consumption. Multiple linear regression models assessed factors predictive of intake. Least square estimates were based on final models and logistic regression determined factors predictive of recommended intake. RESULTS: Ninety-three percent of the participants exceeded the recommended amount of percent calories from fat, 85 % exceeded the saturated fat recommendation, and 92% consumed too much sodium. Also, less than half met the minimum recommended servings of fruit, vegetables, dairy, and grains. CONCLUSIONS: These participants with pre-existing diabetes fell short of consuming foods that met recommended food and nutrition guidelines. These overweight adults diagnosed with diabetes are exceeding recommended intake of fat, saturated fats, and sodium which may contribute to increasing their risk of cardiovascular disease and other chronic diseases.